Crucible of war the Seven Year's War and of fate of empire in British North America 1754-1766 - Anderson, Fred 1949- (Vintage Books, 2001)
"With the Seven Years' War, Great Britain decisively eliminated French power north of the Caribbean - and in the process destroyed an American diplomatic system in which Native Americans had long played a central, balancing role-permanently changing the political and cultural landscape of North America." "Anderson reveals the clash of inherited perceptions the war created when it gave thousands of American colonists their first experience of real Englishmen and introduced them to the British cultural and class system. The war taught George Washington and other provincials profound emotional lessons, as well as giving them practical instruction in how to be soldiers." "Depicting the subsequent British efforts to reform the empire and American resistance - the riots of the Stamp Act crisis and the nearly simultaneous pan-Indian insurrection called Pontiac's Rebellion - as postwar developments rather than as an anticipation of the national independence that no one knew lay ahead (or even desired), Anderson re-creates the perspectives through which contemporaries saw events unfold while they tried to preserve imperial relationships.